Հայոց ազգագրության թանգարանի դաջազարդ գործվածքի նմուշների գեղարվեստական հարդարանքը - Մխիթարյան, Անի (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В коллекции «Текстиль» Армянского этнографического музея сохранились образцы набивных тканей из разных этнорегионов, выполненных с использованием разных технологий набойки и различных форм их художественного декорирования. Коллекция образцов (около 30) отражает их технику и стилистические особенности декора. Используемые в них декоративные решения позволяют определить распространенную и принятую методику разработки как специфической декорации данного региона, так и методики декорации, происходящие из сохраненных образцов тканей форзацев рукописных книг средневековья. Some samples of block printed fabrics from different regions are preserved in the “Textile” collection of the Armenian Ethnography Museum, which are made with different techniques of block-painting and various forms of artistic decoration. The collection of samples (about 30) reflects their technique and stylistic features of the decor. The decorative solutions used in them make it possible to determine the widespread and accepted methodology for the elaboration of both a specific design for a given region and decoration methods originating from preserved samples of fabric book covers of earlier periods.
Keywords: Ազգագրություն